2007
DOI: 10.2116/analsci.23.523
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive HPLC Method for the Simultaneous Determination of Paraquat and Diquat in Human Serum

Abstract: A rapid and sensitive HPLC method for the simultaneous determination of paraquat and diquat in human serum has been developed. After deproteinization of the serum with 10% trichloroacetic acid, the samples were separated on a reversedphase column, and subsequently reduced to their radicals with alkaline sodium hydrosulfite solution. These radicals were monitored with a UV detector at 391 nm. This method permitted the reliable quantification of paraquat over linear ranges of 50 ng -10 μg/ml and 100 ng -10 μg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…PQ can be separated by HPLC using aqueous mobile phases containing methanol, acetonitrile or ion pairing agents [21][22][23]. Several combinations of acetonitrile and 0.1 M (pH 3.0) orthophosphoric acid buffer were evaluated as possible mobile phases.…”
Section: Chromatographic Separationsmentioning
confidence: 99%
See 1 more Smart Citation
“…PQ can be separated by HPLC using aqueous mobile phases containing methanol, acetonitrile or ion pairing agents [21][22][23]. Several combinations of acetonitrile and 0.1 M (pH 3.0) orthophosphoric acid buffer were evaluated as possible mobile phases.…”
Section: Chromatographic Separationsmentioning
confidence: 99%
“…The lower detection limit of our method was 0.01 g/ml. The sensitivity is approximately two times higher than those of most HPLC methods [20][21][22] and the sensitivity was sufficient for the assessment of the prognostic significance of the plasma -PQ concentrations in poisoned patients. Paixao et al [13] had reported a similar method, but our LOD was approximately 10× lower than theirs.…”
Section: Quantitative Analysis Of Pq In Human Plasmamentioning
confidence: 99%
“…Most of the recently published methods for diquat determination are based on liquid [4][5][6][7][8][9] and gas chromatography [10], but despite of their high selectivity and sensitivity, all of them require highly expensive reagents and instrumentation, moreover timeconsuming extraction and separation procedures are also necessary, which make these methods not appropriate for routine analysis. Analyses based on voltammetry have been also performed for diquat determination; in one of them [11] square wave voltammetry was employed, but the limit of detection was an order of magnitude more than the obtained in the herein reported method.…”
Section: Fig1 Molecular Structure Of Diquatmentioning
confidence: 99%
“…This study was carried out at room temperature using the flow assembly depicted in the figure 2, but channel 1 of the manifold was splitted into two lines, one of which was used to test the effect of different media. The tested oxidants were 5x10 -4 M KMnO 4 , Ce(IV) and KIO 4 4 , 0.1 M NaOH and water. As it was previously known that diquat is photochemically decomposed by UV radiation [23], pesticide insertions were performed with and without previous irradiation in order to check its effect, provided that its positive effect on the CL emission have been widely reported [24].…”
Section: Preliminary Studymentioning
confidence: 99%
“…Well-known analytical techniques, such as HPLC,G C-MS, flow-injection spectrophotometry,s urface-enhanced Raman scattering( SERS), and TLC with flame-ionization detection, are efficient but time-consuming and involve elaborate and costly experimental set-up and tedious sample-preparation techniquest hat often limit their applicability in practical use. [6][7][8][9][10][11] Moreover,a nalyzing these toxic chemicalsi nr emote places requires simpler methods that don'ti nvolvec umbersome procedures or expensive instruments. In this respect, optical sensors take priority over other techniques, owing to their simplicity, cost effectiveness, and facile sample preparation.…”
Section: Introductionmentioning
confidence: 99%